Edukasi Pola Hidup Sehat Pada Generasi Z Dalam Meningkatkan Kebugaran Jasmani - Sri Novayanti; Mirza; Imran Fadhil; Agung Cahyadi; Muhammad Idrus (Program Studi Pendidikan Jasmani, Universitas Samudra, 2026)
A healthy lifestyle is one of the important factors in maintaining and improving physical fitness, especially among Generation Z, who are closely associated with the rapid development of digital technology and tend to adopt a sedentary lifestyle. This community service activity aimed to increase the knowledge and awareness of Generation Z regarding the importance of implementing a healthy lifestyle to improve physical fitness. The activity was conducted in Lueng Baro Village, Peusangan Selatan District, Bireuen Regency, through health education methods in the form of counseling and interactive discussions. The activity successfully enhanced participants' understanding and awareness of the importance of adopting a healthy lifestyle through balanced nutrition, adequate physical activity, sufficient rest, and effective stress management to maintain and improve physical fitness. Therefore, healthy lifestyle education can serve as an effective effort to increase awareness and encourage Generation Z to adopt healthy behaviors in their daily lives.